"بانگ درا " کے فکری مباحث: "Bang e Dara’s " Intellectual Debates - Dr. Yasmeen Kausor (Tashkeel e Jadeed, 2025)
Iqbal is a multifaceted personality who is not only a poet and writer but also a philosopher, thinker, politician, educationist, who through his revolutionary poetry awakened the Muslims of India from their slumber and prepared them for the struggle for freedom. The regular evolution of Iqbal's thought and its various aspects can be seen in "Bang e Dara". Allama is a poet who has written on very important topics of life and expressed his thoughts on them with great success. He provided excellent guidance to Muslims. Iqbal's first Urdu collection of poetry "Bang e Dara" was published in front of the literary readers in 1924. He compiled this collection with great effort and published it by repeatedly editing poems and Ghazals which people loved. There were many reasons for its fame. The topics and styles adopted in this book have many new aspects. Iqbal's brilliance is that he mixed tradition and innovation and left his mark, which became Iqbal's special identity. Following Iqbal's unique style of writing, many others tried to imitate this style and style of writing, but those attempts failed. The abilities, talents and knowledge that Allah had given to Iqbal are not in the fortune of every person. Geniuses like Iqbal are born after centuries.